1998
DOI: 10.1159/000055487
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the Inducible Heat Shock Protein 70 mRNA Level in Rat Retina After Ischemia and Reperfusion

Abstract: The heat shock protein 70 (HSP-70) mRNA level was evaluated in Long Evans rat retinas after ischemia and after reperfusion following ischemia. Retinal ischemia was induced by ligation of the optic nerve and vessels. Rats were sacrificed after 90 min of ischemia or 120 min of reperfusion following ischemia. Retinas were dissected. Total mRNA was extracted and inducible HSP-70 (iHSP-70) gene expression was analyzed by quantification of transcripts using an RT-PCR assay. Results were expressed in arbitrary units … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…[24][25][26] In ocular tissue, especially the retina, hsp70 is a major stress protein. Hsp70 in mice is composed of the end products of hsp70.1, 70.2, and 70.3 [18][19][20][21] and has retinal protective effects against various stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] In ocular tissue, especially the retina, hsp70 is a major stress protein. Hsp70 in mice is composed of the end products of hsp70.1, 70.2, and 70.3 [18][19][20][21] and has retinal protective effects against various stresses.…”
Section: Discussionmentioning
confidence: 99%
“…29 However, mRNA expression is strong evidence of protein production. Because the hsp70s from hsp70.1 and hsp70.3 are highly homologous, [18][19][20][21] it is very difficult to distinguish between them at the protein level. Therefore, the production patterns of hsp70s from hsp70.1 and hsp70.3 were evaluated indirectly from the changes in mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…HSPs 25/27 are controversial in the literature; HSP 25 is also reported to be highly specific for the rodent form and does not cross‐react with other HSPs, including primate HSP 27 31 . Many other laboratories have investigated HSP 27 in rats 18,20,22,27,32 . Lewden showed increased HSP 70 mRNA levels by quantification of transcripts using an RT‐PCR assay after 90–120 min ischaemia induced by ligation of the optic nerve, suggesting a rapid HSP‐70 mRNA expression in the retina 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In the retina, a protective role for HSPs against lightinduced retinal injury has been shown in vivo [18], and induced HSP70 increases tolerance to hypoxia and exocytotoxicity in cultured rat retinal ganglion cells [19]. Recently, it has been shown that the HSP70 mRNA level was increased in rat retinas by ischemia-reperfusion [20], but it was still unclear in which cells HSP70 is expressed in this model. Our data clearly demonstrated that HSP70 was significantly increased by ischemia-reperfusion in rabbit retinas and expressed mainly in the Müller cell.…”
Section: Discussionmentioning
confidence: 99%